International Law and Sexual Violence in Armed Conflicts - Eboe-Osuji, Chile (International Humanitarian Law Series, 2012)
Sexual violence is a particular brand of evil that women have endured—more than men—during armed conflicts, through the ages. It is a menace that has continued to challenge the conscience of humanity—especially in our times. At the international level, basic laws aimed at preventing it are not in short supply. What is needed is a more conscious determination to enforce existing laws. This book explores ways of doing just that; thereby shoring up international legal protection of women from sexual violence in armed conflicts.